ANALISIS BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA BEAT (Studi Kasus Pada Mahasiswa Universitas Muhammadiyah Jember) - Kurniawan, Alex; Sumowo, Seno; Puspitadewi S, Ira (Relawan Jurnal Indonesia, 2022)
This study aims to examine and analyze the effect of brand equity (brand awareness, brand association, perceived quality and brand loyalty) on purchasing decisions for Honda Beat products at Muhammadiyah University Jember students. Honda Beat products are now quite a trend among young people, especially students. Brand equity or brand equity is the variable raised in this study because it is a set of brand assets and liabilities related to a brand, its name and symbol, which increase or decrease the value provided by an item or service to the company or the company's customers. This type of research is causality research. The population in this study were students from the Muhammadiyah University of Jember who used Honda Beat motorcycles. The sample used was 75 respondents. The analysis tool uses multiple linear regression. The results of the study prove that brand equity (brand awareness, brand association, perceived quality and brand loyalty) has a significant partial and simultaneous effect on purchasing decisions for Honda Beat products for students at the Muhammadiyah University of Jember.